Therapeutic efficacy of fecal microbiota transplantation in severe food intolerance: a case report - Huang, Yanhui; Huang, Jiayuan; Li, Yuange; Xu, Tianyu; Quan, Guoqiao; Xu, Peihao; Yang, Xiaoya; Liu, Zhou; Xie, Wenrui (Frontiers in Nutrition, 2025)
This report presents the first documented application of fecal microbiota transplantation (FMT) for the management of extensive multi-food intolerance involving 52 specific foods in a pediatric patient with autism spectrum disorder (ASD). A 7 years-old autistic child was diagnosed with food intolerance to 52 items, presenting with generalized rashes, diarrhea, and malnutrition (BMI of 12.9) upon exposure or ingestion of the implicated foods. The child received oral fecal microbiota capsule treatment, with a daily dose of nine capsules (a total of 120 capsules per course) for two consecutive treatment courses. The rashes resolved, the child regained tolerance to previously intolerable foods, nutritional status improved, and stool consistency normalized. This case suggests that FMT may hold therapeutic potential for managing food intolerance in autistic patients.